Analisis Faktor-Faktor Yang Mempengaruhi Pertumbuhan Asuransi Syariah di AJS Bumiputera 1912 Kantor Wilayah Medan - Aprilia, Dita; Syahriza, Rahmi (Universitas Labuhanbatu, 2021)
The movement of Islamic insurance growth as one of an Islamic finance instruments is not as fast as the growth of Islamic banking. Nevertheless, it shows a significance growth wether in the world or Indonesia. In the debate over the legal status of insurance, the insurance based on mutual help and free of ribÃ¢ can be an alternative for those who want a lawful economic transactions. The increasing public appreaciation of the Islamic economic system allows the growth of Islamic insurance in the future rapidly.